Therapy optimization in patients with heart failure: the role of the wearable cardioverter-defibrillator in a real-world setting - Röger, Susanne; Rosenkaimer, Stephanie L.; Hohneck, Anna; Lang, Siegfried; El-Battrawy, Ibrahim; Rudic, Boris; Tueluemen, Erol; Stach-Jablonski, Ksenija; Kuschyk, Jürgen; Akın, Ibrahim; Borggrefe, Martin (BMC cardiovascular disorders, 2018)
The wearable cardioverter-defibrillator (WCD) has emerged as a valuable tool to temporarily protect patients at risk for sudden cardiac death (SCD). The aim of this study was to determine the value of the WCD for therapy optimization of heart failure patients. One hundred five consecutive patients that received WCD between 4/2012 and 9/2016 were included in the study. All patients were followed for clinical outcome and echocardiographic parameters during WCD therapy and had continued follow-up after WCD therapy, irrespective of subsequent implantable cardioverter-defibrillator (ICD) implantation. The most common indication for WCD were newly diagnosed ischemic (ICM) or non-ischemic cardiomyopathy (NICM) with left ventricular ejection fraction (LVEF) ≤35%. Mean WCD wear time was 68.8 ± 50.4 days with a mean daily use of 21.5 ± 3.5 h. Five patients (4.8%) received a total of five appropriate WCD shocks. During WCD wear, patients with ICM and NICM showed significant improvement in LVEF, reducing the proportion of patients with a need for primary preventive ICD implantation to 54.8% (ICM) and 48.8% (NICM). An ICD was finally implanted in 51.4% of the study patients (24 trans-venous ICDs, 30 subcutaneous ICDs). After discontinuation of WCD therapy, all patients were followed for a mean of 18.6 ± 12.3 months. 5.6% of patients with implanted ICDs received appropriate therapies. No patient with subcutaneous ICD needed change to a trans-venous device. None of the patients without an implanted ICD suffered from ventricular tachyarrhythmias and no patient died suddenly. In patients with NICM a significant LVEF improvement was observed during long-term follow-up (from 34.8 ± 11.1% to 41.0 ± 10.2%). WCD therapy successfully bridged all patients to either LVEF recovery or ICD implantation. Following WCD, ICD implantation could be avoided in almost half of the patients. In selected patients, prolongation of WCD therapy beyond 3 months might further prevent unnecessary ICD implantation. The WCD as an external monitoring system contributed important information to optimize device selection in patients that needed ICD implantation.